2019
DOI: 10.2147/dddt.s220396
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effect Of Vasicine Against Myocardial Infarction In Rats Via Modulation Of Oxidative Stress, Inflammation, And The PI3K/Akt Pathway</p>

Abstract: BackgroundMyocardial infarction is the leading cause of damage to the heart and is classified as a major cause of death related to cardiovascular disease. In the present study, we intended to investigate the protective effect of vasicine (VAS) against myocardial infarction in rats, and its mechanism.MethodsMyocardial infarction was induced by isoproterenol (ISO, 100 mg/kg) at an interval of 24 h for 2 days. Different doses of VAS (2.5, 5, and 10 mg/kg body weight) were administered to the rats. The effect of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…The ISO-induced MI group showed numerous ECG alterations, presence of an infarct area, increase in the levels of cardiac enzymes, moderate-to-severe myocardial necrosis, edema, and extensive immune cells infiltration. It has been previously reported that ISO causes detrimental cardiac effects, including necrosis, apoptosis, mitochondrial modifications, oxidative injury, and inflammatory cell infiltration, comparable to what is observed in the ischemic human heart [ 8 , 23 , 25 , 26 ]. Compared to ISO-challenged animals, geraniol pretreatment led to a size reduction of the infarct region, attenuation of cardiac indicator enzymes, as well as diminished myocardial necrosis, edema, and immune cells infiltration.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The ISO-induced MI group showed numerous ECG alterations, presence of an infarct area, increase in the levels of cardiac enzymes, moderate-to-severe myocardial necrosis, edema, and extensive immune cells infiltration. It has been previously reported that ISO causes detrimental cardiac effects, including necrosis, apoptosis, mitochondrial modifications, oxidative injury, and inflammatory cell infiltration, comparable to what is observed in the ischemic human heart [ 8 , 23 , 25 , 26 ]. Compared to ISO-challenged animals, geraniol pretreatment led to a size reduction of the infarct region, attenuation of cardiac indicator enzymes, as well as diminished myocardial necrosis, edema, and immune cells infiltration.…”
Section: Discussionmentioning
confidence: 85%
“…Autophagy is a type II cell death mechanism, which is known to be involved in the pathophysiological process of MI; therefore, the modulation of autophagy may be considered as a therapeutic strategy for MI [ 26 ]. Previous studies established that compounds that modulate PI3K/Akt signaling can exhibit cardioprotective actions [ 8 , 26 ]. Akt phosphorylation has been found to prevent apoptosis and promote cell survival in the ischemic heart [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copious amount of evidence infers that any agent which could modulate or regulate PI3K/Akt signaling pathway may display myocardial protection (cardioprotective) by inhibiting oxidative stress and apoptosis (Jiang et al., 2019; Yang et al, 2019). Hence, we speculate that TAN might also, modulate PI3K/Akt pathway and thus favor cardioprotective activity against the ISP‐induced MI model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lu et al (2018) confirmed the cardioprotective activity of TAN against heart failure (MI) in the rat model, but they failed to explore the in‐depth molecular mechanism. Copious studies have demonstrated that any agent in which modulation or regulation PI3K/Akt signaling pathway might involve in myocardial protection (cardioprotective) by inhibiting oxidative stress and apoptosis (Jiang, Zhang, Ding, & Li, 2019; Yang et al, 2019). Hence, we hypothesize that TAN might also, modulate PI3K/Akt pathway and thus favor cardioprotective activity against the isoproterenol (ISP)‐induced MI model.…”
Section: Introductionmentioning
confidence: 99%